Tests für den M. subscapularis - Klien, Sebastian (MSK – Muskuloskelettale Physiotherapie, 2021)
Dakkak A, Krill MK, Krill ML et al. Evidence-Based Physical Examination for the Diagnosis of Subscapularis Tears: A Systematic Review. Sports Health 2021; 13: 78–84. doi:10.1177/1941738120936232